Mechanical stress activates neurites and somata of myenteric neurons - Kugler, Eva M.; Michel, Klaus; Zeller, Florian; Demir, Ihsan E.; Ceyhan, Güralp O.; Schemann, Michael; Mazzuoli-Weber, Gemma (Frontiers in Cellular Neuroscience, 2015)
The particular location of myenteric neurons, sandwiched between the 2 muscle layers of the gut, implies that their somata and neurites undergo mechanical stress during gastrointestinal motility. Existence of mechanosensitive enteric neurons (MEN) is undoubted but many of their basic features remain to be studied. In this study, we used ultra-fast neuroimaging to record activity of primary cultured myenteric neurons of guinea pig and human intestine after von Frey hair evoked deformation of neurites and somata. Independent component analysis was applied to reconstruct neuronal morphology and follow neuronal signals. Of the cultured neurons 45% (114 out of 256, 30 guinea pigs) responded to neurite probing with a burst spike frequency of 13.4 Hz. Action potentials generated at the stimulation site invaded the soma and other neurites. Mechanosensitive sites were expressed across large areas of neurites. Many mechanosensitive neurites appeared to have afferent and efferent functions as those that responded to deformation also conducted spikes coming from the soma. Mechanosensitive neurites were also activated by nicotine application. This supported the concept of multifunctional MEN. 14% of the neurons (13 out of 96, 18 guinea pigs) responded to soma deformation with burst spike discharge of 17.9 Hz. Firing of MEN adapted rapidly (RAMEN), slowly (SAMEN) or ultra-slowly (USAMEN). The majority of MEN showed SAMEN behavior although significantly more RAMEN occurred after neurite probing. Cultured myenteric neurons from human intestine had similar properties. Compared to MEN, dorsal root ganglion neurons were activated by neurite but not by soma deformation with slow adaptation of firing. We demonstrated that MEN exhibit specific features very likely reflecting adaptation to their specialized functions in the gut.